IR Image Upconversion Under Dual-Wavelength Laser Illumination - H. Maestre; A. J. Torregrosa; J. Capmany (IEEE Photonics Journal)
We investigate the use of dual-wavelength laser illumination in a nonlinear infrared-to-visible image upconversion system. We show how a two-wavelength laser illumination can combine the enhanced upconversion field-of-view (FOV) characteristic of broadband thermal or amplified spontaneous emission (ASE) illumination with the higher power intensity of a laser. By properly choosing the wavelength spectral spacing of only two laser wavelengths and their relative amplitudes, the FOV that can be upconverted in the nonlinear crystal can be enlarged up to an extent similar to broadband illumination and intensity homogenized. In this way, a step is taken towards image upconversion beyond the lab to practical longer range illumination-assisted outdoor applications. We provide an experimental verification in good agreement with our model's simulations for original infrared images in the eye-safe spectral region around 1550 nm upconverted to around 631 nm in a periodically poled LiNbO $_{3}$ crystal.